2018
DOI: 10.1111/1744-9987.12656
|View full text |Cite
|
Sign up to set email alerts
|

Super High‐Flux Continuous Venovenous Hemodialysis Using Regional Citrate Anticoagulation: Long‐Term Stability of Middle Molecule Clearance

Abstract: Continuous renal replacement therapy is a standard treatment in critically ill patients with acute kidney injury. All CRRT techniques provide a high low-molecular weight clearance but even with hemofiltration, clearance of middle molecules is low. We investigated whether a new super high-flux hemofilter provides effective and sustained middle molecule clearance during citrate-anticoagulated continuous venovenous hemodialysis for up to 72 h. We included 14 critically ill patients with AKI-KDIGO-III in a prospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 28 publications
2
10
0
Order By: Relevance
“…Better clearance of β 2 -microglobulin in the intervention arm in this study is in line with the results of others [17,28,41]. Contrary to these findings, another small cohort (n = 10), which compared the β 2 -microglobulin clearance between CVVHDF using high-flux and HCO dialyzers, showed no difference in both study arms, although the dialysis dose was much higher in the CVVHDF arm (36 ± 4 ml/kg/h) than in the CVVHD arm (21 ± 6 ml/ kg/h) [29].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Better clearance of β 2 -microglobulin in the intervention arm in this study is in line with the results of others [17,28,41]. Contrary to these findings, another small cohort (n = 10), which compared the β 2 -microglobulin clearance between CVVHDF using high-flux and HCO dialyzers, showed no difference in both study arms, although the dialysis dose was much higher in the CVVHDF arm (36 ± 4 ml/kg/h) than in the CVVHD arm (21 ± 6 ml/ kg/h) [29].…”
Section: Discussionsupporting
confidence: 92%
“…A good clearance of β 2 -microglobulin was demonstrated in chronic dialysis patients using dialyzers with increased pore size [26,27]. Recent studies have also confirmed a good clearance for middle molecules in CVVHD with RCA and HCO dialyzers in critically ill patients [17,28].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Inconsistently, the ultrafiltrate from patients with heart failureproduced a positive inotropic response potentially attributable to catecholamines [26]. Furthermore, Siebeck M et al [27] indicated that the catecholamine concentration was significantly decreased after continuous hemofiltration. Given that adrenalin (molecular weight: 219) and dopamine (molecular weight: 153) are “small” molecules, we speculated that adrenalin and dopamine may be removed directly by CVVHDF.…”
Section: Discussionmentioning
confidence: 99%
“…Regional Citrate Anticoagulation (RCA) is the Kidney Disease-Improving Global Outcome (KDIGO) recommended anticoagulation of choice for continuous renal replacement therapy and is of particular value to patients with contraindications to heparin and high risk of bleeding such as those who have undergone cardiac surgery [3,4]. RCA is also associated with a prolonged filter life-span due to a decreased incidence of clotting and preservation of the filter sieving coefficient for larger molecules including inflammatory mediators [5,6]. This anticoagulation modality was reported to be safe and preferred after cardiac surgery [7].…”
Section: Introductionmentioning
confidence: 99%